SYNTHESIS,ANTIBACTERIAL ACTIVITY OF 2-AMINO 5-PHENYL -1,3,4- OXADIAZOLE DERIVATIVES - Hussain jassem Mohammed (مجلة بغداد للعلوم, 2008)
In the present investigation, five derivatives were synthesized as potential  antimicrobial   agents , The compounds  are : 2-amino 5-phenyl - 1,3,4-  oxadiazole  dithi-ocarbomate, 2-amino 5-( 4-amino- N,N-dimethyl phenyl)-  1,3,4- oxadiazole,    2-amino 5- (4-amino N,N- dimethyl phenyl)- 1,3,4- oxadizole  dithiocarbamate, 2-amino 5-(4-nitr-ophenyl)-1,3,4-oxadiazole, 2-amino 5-(4-nirophenyl)-1,3,4- oxadiazole  dithiocarbamate.